: - Abdullah Abdullah; Khairil Khairil; Hafnati Rahmatan; Khairunnisa Khairunnisa (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the application of the problem-based learning model combined with flashcard media has an effect on students' creative thinking skills. The method used in this research is a quasi-experimental method. This research was conducted in two Madrasah Aliyah, Banda Aceh City, Aceh, Indonesia. The research was conducted in the even semester of the 2019/2020 Academic Year. The research sample was taken by purposive sampling as many as 126 students, namely the experimental group 63 and the control group 63. The parameters measured in the study were students' creative thinking skills. Creative thinking skills data were analyzed using quantitative descriptive by converting ordinal data into intervals through interval successive method (ISM) and ANCOVA test. The results showed that there was an effect of students' creative thinking skills using a problem-based learning model combined with flashcard media. The conclusion of this study is that the application of the problem-based learning model combined with flashcard media has an effect on students' creative thinking skills on Environmental Pollution material in MAN 1 and MAN 2 Banda Aceh City